Growth and Results of Strobery Plants (Fragaria chiloensis, L) in Various Types of Organic Mulch and Plant Media - Khadijah Khadijah (University of Darussalam Gontor, Ponorogo, East Java Indonesia, 2019)
Strawberry (Flagaria chiloensis, L.) is a herbaceous plant thatpropagates, the fruit contains lots of fiber, vitamin C, folic acid, potassium and antioxidant. The research was conducted in the experimental field of the Agriculture Faculty, Gajah Putih University, Blang Bebangka, Pagasing District, Central Aceh Regency with a height of ± 1,150 m above sea level, soilpH 5.5 – 6.0. This research was conducted in February until April 2018. The research used factorial randomized block design (RBD) with two factors. The first factor is organic mulch consisting of 4 levels, (M0) = No mulch (control); (M1) = wood sawdust mulch; (M2) = rice husk mulch; (M3) = waste coffee mulch. The second factor is the ratio of planting media (kg) which consists of 4levels,(T1) = soil, sand, manure (7: 1: 2); (T2) = soil, sand, manure (6: 1: 3); (T3) = soil, sand, manure (4: 2: 4); (T4) = soil, sand, manure (3: 2: 5).The results of this study indicate that wood sawdust mulch produces the average number of tillers (6.25 children) and the best strawberry fruit weight (65.66 g per clump) from organic mulch treatment. Comparison of planting media, soil, sand and manure (3: 2: 5) produces the number of tillers (7.5 tillers) and strawberry fruit weight (76.73 g per clump) which is the best from the comparison treatment of planting media. The combination treatment of comparison of planting media, soil, sand and manure (3: 2: 5) with organic mulch treatment produces the best average number of tillers and strawberry fruit weight from the treatment combination.